1996
DOI: 10.1111/1523-1747.ep12345532
|View full text |Cite
|
Sign up to set email alerts
|

The Same Dominant T Cell Clone Is Present in Multiple Regressing Skin Lesions and Associated T Cell Lymphomas of Patients with Lymphomatoid Papulosis

Abstract: This study was undertaken to determine the clonality of lymphomatoid papulosis (LyP), its clonal relationship to lymphomas, which occur at high frequency in LyP patients, and to define the cell lineage of Reed-Sternberg-like cells in type A lesions of LyP. Punch biopsies of skin of 11 adult patients with LyP were analyzed for morphologic subtype of LyP, surface antigens, and clonal T-cell receptor (TCR) gene rearrangements. Clonal rearrangements were identified by semiquantitative polymerase chain reaction amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 25 publications
4
68
0
3
Order By: Relevance
“…3 It was shown that LyP cases with associated lymphomas shared the same clonal rearrangement in most instances. 6,[9][10][11][12] Several attempts to demonstrate the presence of clonal T-cell populations in LyP lesions without complicating T-cell lymphomas, however, produced conflicting results. 11,[13][14][15][16] This might, besides the clinical benign course, be one reason why LyP is For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 It was shown that LyP cases with associated lymphomas shared the same clonal rearrangement in most instances. 6,[9][10][11][12] Several attempts to demonstrate the presence of clonal T-cell populations in LyP lesions without complicating T-cell lymphomas, however, produced conflicting results. 11,[13][14][15][16] This might, besides the clinical benign course, be one reason why LyP is For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11][12] Several attempts to demonstrate the presence of clonal T-cell populations in LyP lesions without complicating T-cell lymphomas, however, produced conflicting results. 11,[13][14][15][16] This might, besides the clinical benign course, be one reason why LyP is For personal use only. on April 3, 2019. by guest www.bloodjournal.org From still assigned to the heterogeneous group of cutaneous pseudolymphomas, a group of benign reactive lymphoproliferative processes that clinically and/or histologically mimic cutaneous lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of the underlying mechanism is poorly understood, with some theories relating to monotypic expansion of activated T cells that occurs with solid tumors, and it is possible that T cell lymphoma originates from cytotoxic CD30+ T cell expansion [20]. Secondary genetic abnormalities probably lead to the dominance of a T cell clone, leading to irreversible transformation to lymphoma [21]. Whether ALCL predisposes to, or is merely associated with papillary carcinoma, is still a controversial issue which requires a more detailed consideration.…”
Section: Discussionmentioning
confidence: 99%